Management and Clinical Outcome of Penetrating Keratoplasty for Long-Term Corneal Changes in Sympathetic Ophthalmia - Saraswathi Ramamurthi; Ebube E. Obi; Gordon N. Dutton; Kanna Ramaesh (Journal of Ophthalmology)
Purpose. To report the visual outcome of penetrating keratoplasty performed on the sympathizing eye in three cases of sympathetic ophthalmitis. Methods. Interventional case series of three patients, diagnosed with sympathetic ophthalmitis, with corneal changes in the form of band keratopathy and decompensation underwent penetrating keratoplasty to the sympathizing eye. They had each sustained penetrating trauma as a child and had undergone previous cataract surgery and superficial keratectomy. Two patients had undergone lamellar keratoplasty prior to this procedure. One patient had undergone trabeculectomy for glaucoma, and she was on antiglaucoma medication. The preoperative visual acuity was 1/60 in the affected eye of each patient. Penetrating keratoplasty was performed in the sympathizing eye and the donor graft size was 7.50 mm, and the host graft size was 7.25 mm. Our patients were immunosuppressed prior to the procedure to help prevent graft rejection. Result. At one year follow-up, a BCVA of 6/36 or better was achieved in all three patients. Postoperative examination of the fundus showed peripheral chorioretinal atrophy with pigmentary changes at the macula, accounting for the limited vision. The grafts remain clear to date, and there has been no recurrence of uveitis or rejection. Conclusion. Penetrating keratoplasty can be considered as a surgical option to restore useful vision in a stable sympathizing eye in sympathetic ophthalmitis, and this depends on the extent of the pathology. However, these cases require treatment with immunosuppressives to prevent graft rejection and to prolong graft survival.